Diplomasi Ekonomi Indonesia di dalam Rezim Ekonomi G20 pada Masa Pemerintahan Joko Widodo - Wiwiek Rukmi Dwi Astuti; Laode Muhamad Fathun; Laode Muhamad Fathun, Laode Muhamad (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2020)
This research answers how Indonesia's economic diplomacy strategy is in the G20 global economic forum. This research uses a qualitative approach, literature study and the concept of economic diplomacy to analyze the data. The results show that Indonesia's diplomacy strategy which is implemented through the national strategic plan in the G20 forum forms a pattern of economic diplomacy regarding trade, commerce and finance. The novelty of this research is to prove the character of Indonesia's economic diplomacy in the G20 forum as a country that is in an evolving cluster. External economic management and policies through coordination between ministries; trade promotion which is an integration of political and economic efforts; the Ministry of Foreign Affairs to actively promote investment, particularly through the ambassador and BKPM. The role and diplomacy of Indonesia's economy is a commitment to maintaining national, regional and international economic stability as a form of national and international interests.